2013
DOI: 10.1093/jac/dkt492
|View full text |Cite
|
Sign up to set email alerts
|

Report of ribosomal RNA methylase gene erm(B) in multidrug-resistant Campylobacter coli

Abstract: To the best of our knowledge, this is the first report of a horizontally transferable macrolide resistance mechanism in thermophilic Campylobacter. Surveillance of erm(B) and its associated MDRGI in both C. coli and C. jejuni is urgently warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
117
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(126 citation statements)
references
References 35 publications
6
117
1
2
Order By: Relevance
“…The detailed genetic features of the erm(B)-carrying plasmids and their transfer mechanisms remain to be determined in future studies. The identification of multiple erm(B)-positive isolates in this study reinforced the findings in our recent report (11) and indicates that erm(B) has emerged and is disseminating in Campylobacter. This finding is significant, as macrolides are the key antibiotic for clinical therapy of Campylobacter infections and resistance mediated by rRNA methylase was not identified until recently (11).…”
Section: Erm(b) In Campylobactersupporting
confidence: 90%
See 4 more Smart Citations
“…The detailed genetic features of the erm(B)-carrying plasmids and their transfer mechanisms remain to be determined in future studies. The identification of multiple erm(B)-positive isolates in this study reinforced the findings in our recent report (11) and indicates that erm(B) has emerged and is disseminating in Campylobacter. This finding is significant, as macrolides are the key antibiotic for clinical therapy of Campylobacter infections and resistance mediated by rRNA methylase was not identified until recently (11).…”
Section: Erm(b) In Campylobactersupporting
confidence: 90%
“…Our previous study showed that the type I MDRGI from ZC113 could be transferred to C. jejuni NCTC 11168 via natural transformation (11). In this study, we examined five other types of MDRGIs and found that they were also transferable from C. coli isolates to C. Table 2).…”
Section: Erm(b) In Campylobactermentioning
confidence: 78%
See 3 more Smart Citations